Foreign exchange interventions and their impact on expectations: Evidence from the USD/ILS options market - Markus Hertrich; Daniel Nathan (Deutsche Bundesbank, 2022)
Using confidential daily data, we analyse how the intervention episode of the Bank of Israel (BOI) from 2013 to 2019 has affected the foreign value of the Israeli new shekel (ILS) and the expectations about its future value. We find that interventions amounting to US dollar (USD) 1 billion are on average associated with a depreciation of the ILS by 0.82%-0.85%, which is at the upper bound of the estimated impact in other studies. The (indirect) effect on the forward rate is smaller - the BOI's USD purchases have widened the negative deviation from covered interest parity. The higher moments of the risk-neutral probability distribution of future exchange rates proxied by the scaled price quotes of USD/ILS options, on the contrary, are unaffected. The USD purchases simply shift the whole distribution towards higher USD/ILS values. Crash risk, for instance, is unaffected. We also find that the USD/ILS options market anticipates intervention episodes and prices them in before they occur.
Keywords: E52; E58; E65; F31; G14; G15; 330; exchange rate; expectations; central bank intervention; Israeli new shekel; reaction function